2021
DOI: 10.1101/2021.09.08.459430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-related differences in immune dynamics during SARS-CoV-2 infection in rhesus macaques

Abstract: Advanced age is a key predictor of severe COVID-19. To gain insight into this relationship, particularly with respect to immune responses, we utilized the rhesus macaque model of SARS-CoV-2 infection. Two cohorts of eight older (16-23 years) and eight younger (3-5 years) rhesus macaques were inoculated with SARS-CoV-2. Animals were evaluated using viral RNA quantification, clinical observations, thoracic radiographs, single-cell transcriptomics, multiparameter flow cytometry, multiplex immunohistochemistry, cy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
(79 reference statements)
3
8
0
Order By: Relevance
“…A multiomics study comparing subadult and aged rhesus macaques showed that age did not substantially affect acute disease; however, an age-specific divergence of immune responses emerged during the postacute phase of infection (7 to 21 dpi). As in humans, advanced age resulted in a delayed or impaired induction of antiviral cellular immune responses and a delay in the efficient return to immune homeostasis [ 85 ].…”
Section: Age and Comorbiditiesmentioning
confidence: 99%
“…A multiomics study comparing subadult and aged rhesus macaques showed that age did not substantially affect acute disease; however, an age-specific divergence of immune responses emerged during the postacute phase of infection (7 to 21 dpi). As in humans, advanced age resulted in a delayed or impaired induction of antiviral cellular immune responses and a delay in the efficient return to immune homeostasis [ 85 ].…”
Section: Age and Comorbiditiesmentioning
confidence: 99%
“…And this delayed innate immune response subsequently failed to prime an adaptive immune response, the study of Carolina Lucas et al (40) indicated that COVID-19 mortality did not correlated with the crosssectional antiviral antibody levels per se but, rather, with the delayed kinetics of neutralizing antibody(NAb) production. What's more, advanced age has been widely recognized as a significant factor associated with severe disease, multi-omics profiling (41) suggests that age may delay or impair antiviral cellular immune responses and delay efficient return to immune homeostasis. The above data linked the general evidence for the pathogenesis of SARS-CoV-2, for instance, the target: type I and type III IFN; the mechanism: delaying the innate immune responses; the immunological characteristics: the delayed innate immune cell counts and the delayed kinetics of NAb production; and the clinical characteristics: advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…However, older animals showed signs of delayed T cell responses and return to immune homeostasis. 54 De Wit also shared work on animal models for Nipah virus infection and disease. The origin of several human Nipah virus cases was traced to the consumption of date palm sap contaminated with virus from bat excrement.…”
Section: Nhp Models For Coronaviruses and Henipavirusesmentioning
confidence: 99%